Rationalizability of menu preferences - Christopher J. Tyson (Queen Mary University of London, School of Economics and Finance, 2017)
The class of preferences over opportunity sets ("menus") rationalizable by underlying preferences over the alternatives is characterized for the general case in which the dataset is unrestricted. In particular, both the universal set of alternatives and the domain of menus over which preferences are asserted by the decision maker are arbitrary. The key "Cover Dominance" axiom states that any menu strictly preferred to a collection of menus must be strictly preferred to any menu covered by the collection. The method of characterization relies upon transitivity of menu preferences, but completeness can be relaxed.
Keywords: D01; D11; 330; General domains; Opportunity sets; Revealed preference; Transitivity